Get Answers to all your Questions

header-bg qa

Q10 Factorise the following expressions 

(IV)

49 y^2 + 84 yz + 36 z^2

Answers (1)

best_answer

We have, 
                49 y^2 + 84 yz + 36 z^2 = 49y^2 + 42yz + 42yz + 36z^2
                                                          = 7y(7y + 6z) + 6z(7y + 6z)
                                                          = (7y + 6z)(7y + 6z) =  (7y+ 6z)^{2}
Therefore,
                  49y^2+84yz+36z^2=(7y+6z)^2

Posted by

Gautam harsolia

View full answer